Jornal Brasileiro De Doenças Sexualmente Transmissíveis 2021
DOI: 10.5327/dst-2177-8264-202133p012
|View full text |Cite
|
Sign up to set email alerts
|

Human T-cell leukemia virus type 1 infection among Japanese immigrants and their descendants living in Southeast Brazil: a call for preventive and control responses

Abstract: Introduction: Human T-cell leukemia virus type 1 (HTLV-1) has worldwide distribution and is considered endemic in southwestern Japan. HTLV-1 infection has been associated with adult T-cell leukemia/lymphoma (ATL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) besides other diseases. Objective: This cross-sectional study aimed to investigate the prevalence, risk factors, and molecular characterization of HTLV-1, among the world´s largest population of Japanese immigrants and their desce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…HTLV-1 is endemic in South America, affecting 13 countries and prevailing in several ethnic groups. 19 , 20 , 21 In Brazil, HTLV-1 is found in immigrants from endemic areas such as Africa and Japan, 8 , 21 , 22 , 23 their descendants and in the descendants of Amerindians who have inhabited South America for thousands of years. 24 , 25 , 26 Several studies performed in Brazil on large populations of blood donors have found an heterogeneous HTLV-1 seroprevalence ranging from 0.04 to 1% depending on the geographical location.…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-1 is endemic in South America, affecting 13 countries and prevailing in several ethnic groups. 19 , 20 , 21 In Brazil, HTLV-1 is found in immigrants from endemic areas such as Africa and Japan, 8 , 21 , 22 , 23 their descendants and in the descendants of Amerindians who have inhabited South America for thousands of years. 24 , 25 , 26 Several studies performed in Brazil on large populations of blood donors have found an heterogeneous HTLV-1 seroprevalence ranging from 0.04 to 1% depending on the geographical location.…”
Section: Discussionmentioning
confidence: 99%
“…The human T-lymphotropic virus (HTLV) type 1 infection is associated with the development of two main diseases: a malignancy of CD4 + T-cells named adult T-cell leukemia/lymphoma (ATLL) and the HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) ( 1 , 2 ), which is a chronic inflammatory neurodegenerative disease that affects mainly the upper motor neurons in the thoracic spinal cord ( 3 , 4 ). HTLV-1 infection is worldwide distributed but it shows hot spots of endemicity in several countries and regions, including Brazil, Japan, the Caribbean, Central and West Africa, the Middle Eastern, and Australia ( 5 9 ). In recent years, HTLV-1 infection has been also considered a matter of concern as it remains a threat to communities, particularly in low-income countries due to the lack of epidemiological surveillance and control measures but also in association with the rising levels of human migration ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…HTLV-1 infection is worldwide distributed but it shows hot spots of endemicity in several countries and regions, including Brazil, Japan, the Caribbean, Central and West Africa, the Middle Eastern, and Australia ( 5 9 ). In recent years, HTLV-1 infection has been also considered a matter of concern as it remains a threat to communities, particularly in low-income countries due to the lack of epidemiological surveillance and control measures but also in association with the rising levels of human migration ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%